Molecular Crowding Effect in Aqueous Electrolytes to Suppress Hydrogen Reduction Reaction and Enhance Electrochemical Nitrogen Reduction. Issue 36 (6th August 2021) - Guo, Ying; Gu, Jinxing; Zhang, Rong; Zhang, Shaoce; Li, Zhen; Zhao, Yuwei; Huang, Zhaodong; Fan, Jun; Chen, Zhongfang; Zhi, Chunyi
Abstract: The H2 evolution reaction (HER), one of the most intractable issues for the electrochemical N2 reduction reaction (NRR), seriously hinders NH3 production selectivity and yield rate. Considering that hydrogenation reactions are essential to the aqueous NRR process, acidic electrolytes would be an optimum choice for NRR as long as the proton content and the HER kinetics can be well balanced. However, there is a striking lack of strategies available for electrolyte optimization, i.e ., rationally regulating electrolytes to suppress HER and promote NRR, to achieve impressive NRR activity. Herein, a HER‐suppressing electrolytes are developed using hydrophilic poly(ethylene glycol) (PEG) as the electrolyte additive by taking advantage of its molecular crowding effect, which promotes the NRR by retarding HER kinetics. On a TiO2 nanoarray electrode, a significantly improved NRR activity with NH3 Faraday efficiency (FE) of 32.13% and yield of 1.07 µmol·cm −2 ·h −1 is achieved in the PEG‐containing acidic electrolytes, 9.4‐times and 3.5‐times higher than those delivered in the pure acidic electrolytes. Similar enhancements are achieved with Pd/C and Ru/C catalysts, as well as in an alkaline electrolyte, demonstrating a universally positive effect of molecular crowding in the NRR. This work casts new light on aqueous electrolyte design in retarding HER kinetics and expediting the NRR. Abstract : Hydrogen evolution reaction (HER)‐suppressing electrolytes are successfully developed by taking advantage of the molecular crowding effect of the hydrophilic PEG400 additive, which can effectively retard parasitic HER and promotes the desirable nitrogen reduction reaction (NRR), thus achieving exceptional NH3 production. This work casts new light on the aqueous electrolyte design for suppressing the HER and facilitating NH3 selectivity in the NRR.